Baseline health perceptions, dysphagia, and survival in patients with head and neck cancer. Issue 6 (18th December 2013) - Lango, Miriam N.; Egleston, Brian; Fang, Carolyn; Burtness, Barbara; Galloway, Thomas; Liu, Jeffrey; Mehra, Ranee; Ebersole, Barbara; Moran, Kathleen; Ridge, John A.
Abstract : BACKGROUND: In head and neck cancer patients prior to treatment, dysphagia noted by patients is more common than aspiration on formal swallow studies. The authors hypothesized that patient‐reported dysphagia impacts multiple domains of quality of life (QOL) and predicts disease recurrence and disease‐related death. METHODS: The Swal‐QOL, a dysphagia‐specific, swallowing‐related, QOL measure, and the EuroQOL‐5D‐3L were administered to 159 patients before treatment with curative intent in this prospective cohort study. Logistic regression analysis evaluated associations among clinical and subjective measures. Multivariable competing risk regression tested the impact of clinical, tumor, and patient‐reported measures on survival. RESULTS: Baseline dysphagia, pain, and diminished patient‐reported health state were found to be closely associated with weight loss before treatment and advanced T classification. However, only 58% of patients (23 of 40 patients) reporting dysphagia experienced > 5% weight loss. Dysphagia was found to be associated with pain and/or diminished patient‐reported health state, independent of weight loss. Female patients were more likely to report pain and dysphagia, whereas male patients reported dysphagia alone. Dysphagia was found to be predictive of disease recurrence and disease‐related death, adjusting for T and N classifications, ECOG performance status, smoking status, and weight loss, and accounting for competing risks of death (recurrence‐free survival: hazards ratio, 3.8 [95% confidence interval, 1.7‐8.4; P  = .001] and disease‐related death: hazards ratio, 4.2 [95% confidence interval, 1.04‐5; P  = .004]). CONCLUSIONS: Baseline dysphagia affects multiple domains of QOL and general health perceptions in patients with head and neck cancer prior to treatment. A dysphagia measure captures the effort of maintaining nutrition, and identifies patients predisposed to disease recurrence and disease‐related death. Cancer 2014;120:840–847 . © 2013 American Cancer Society . Abstract : Baseline dysphagia affects multiple domains of quality of life and general health perceptions in patients with untreated head and neck cancer. A patient‐reported dysphagia measure captures the effort of maintaining nutrition, and identifies patients predisposed to disease recurrence and disease‐related death.